2013
DOI: 10.1097/spc.0000000000000017
|View full text |Cite
|
Sign up to set email alerts
|

Gut barrier dysfunction and microbial translocation in cancer cachexia

Abstract: Purpose of ReviewCachexia is a complex metabolic syndrome characterized by skeletal muscle and adipose tissue loss and is frequently associated with emaciation, anorexia, systemic inflammation, and metabolic dysfunction. Lack of a clear understanding of the cause of cancer cachexia has impeded progress in identifying effective therapeutic agents. This review summarizes recent publications on the role of gut barrier function, intestinal microbiota, and inflammation in the etiology of cancer cachexia and new the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 74 publications
2
73
1
Order By: Relevance
“…PAF-R are mainly expressed by mesenchymal cells, which may explain the implication of adipose, muscle, liver, and heart tissue, as well as gut barrier and brain dysfunctions in cachexia, supporting our proposed model (31,32,(62)(63)(64). Also, the described crosstalk between wasting of fat tissue and skeletal muscle is compatible with the proposed mechanism (65)(66)(67).…”
Section: Discussionsupporting
confidence: 71%
“…PAF-R are mainly expressed by mesenchymal cells, which may explain the implication of adipose, muscle, liver, and heart tissue, as well as gut barrier and brain dysfunctions in cachexia, supporting our proposed model (31,32,(62)(63)(64). Also, the described crosstalk between wasting of fat tissue and skeletal muscle is compatible with the proposed mechanism (65)(66)(67).…”
Section: Discussionsupporting
confidence: 71%
“…One of these articles described a possible mechanism by which cancer-related cachexia and the GI microbiome are related [58]. This report suggested that cachexia in cancer patients is due to increased intestinal permeability secondary to microbial pathogens and/or intestinal inflammation [58]. As discussed above, chemotherapy can result in increased intestinal permeability, resulting in microbial translocation of gut microbes out of the intestine, which then triggers a systemic immune response [58].…”
Section: The Microbiome and Cachexiamentioning
confidence: 94%
“…A PubMed search for "microbiome and cachexia" yielded 5 results, two of which were relevant for this review. One of these articles described a possible mechanism by which cancer-related cachexia and the GI microbiome are related [58]. This report suggested that cachexia in cancer patients is due to increased intestinal permeability secondary to microbial pathogens and/or intestinal inflammation [58].…”
Section: The Microbiome and Cachexiamentioning
confidence: 96%
“…Interestingly, colonization of the intestine by different strains of bacteria has been shown to modulate disease severity and cachexia development in mouse models (Schieber et al 2015). A role for therapeutic agents targeting intestinal function in CAC remains largely speculative at present (Klein et al 2013). Whether inhibition of browning may indirectly affect tumor metabolism is not known.…”
Section: Role Of Lipids Burning Fat and White Adipose Tissue (Wat) mentioning
confidence: 99%